2015
DOI: 10.1016/j.ajpath.2015.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Endothelial-to-Mesenchymal Transition as a Potential Participant in Radiation Proctitis

Abstract: The endothelial-to-mesenchymal transition (EndoMT) is a crucial cellular process during heart development necessary to the formation of cardiac valves. This embryonic process reappears in several pathological situations, such as vascular injury or organ fibrosis of various etiologies, as a mediator of extracellular matrix-producing cells. Because radiation induces both vascular damage and fibrosis, we investigated whether radiation exposure induces EndoMT in primary human intestinal microvascular endothelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 48 publications
(42 reference statements)
1
24
0
Order By: Relevance
“…In contrast, radiation‐induced models of inflammation have been shown to be controllable and reproducible . We have confirmed these findings in our study, as submucosal or transmural inflammation was observed in all animals in histopathology and MRI.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, radiation‐induced models of inflammation have been shown to be controllable and reproducible . We have confirmed these findings in our study, as submucosal or transmural inflammation was observed in all animals in histopathology and MRI.…”
Section: Discussionsupporting
confidence: 88%
“…EndoMT is involved in organ development and various types of fibrosis. For example, EndoMT contributes to cardiac fibrosis [ 10 12 ], pulmonary fibrosis [ 10 , 13 ], corneal fibrosis [ 14 ], radiation-induced pelvic disease [ 15 ] and inflammatory bowel disease-associated fibrosis [ 16 ]. EndoMT was also found in the early development of kidney interstitial fibrosis in the streptozocin (STZ)-induced diabetic nephropathy (DN) model [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primary human intestinal microvascular endothelial cells (HIMECs) were prepared as described. 21 , 22 HIMECs (passage 4) and human umbilical vein endothelial cells (HUVECs) (passage 3) were transfected as described previously. 23 Briefly, cells were seeded into 6-well plates for 48 hours to reach 50%–70% confluence and were transfected with siRNA (100 nM) using Dharmafect according to the manufacturer’s protocols (Dharmacon, Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%